The Integration of Time-Space Prism and Psychological Mechanism on The Use of Public Transport - Kariuki, Mark; Dharmowijoyo, Dimas; Tanjung, Liza Evianti; Shalihati, Sakinah F. (The Asian Journal of Technology Management (AJTM), 2020)
Abstract. A hierarchical structured equation model and a multi- dimensional 21-day household time-use and activity diary conducted in Bandung Metropolitan Area, Indonesia investigated the interaction among individuals’ psychological mechanism, daily activity participation and built environment in selecting public transport as a mode choice. The preliminary analyses of the collected data indicated that different beliefs, support and attachment to motorised modes significantly relate with different groups of occupation, gender, age, income class, activity participation and activities. Therefore, an individuals’ subjective characteristics and day-to-day time–space components significantly influence their selection of public transport as their preferred mode choice to participate in certain activities. The study results also show how built environment influences individuals’ mandatory and discretionary activity participation in the selection of public transport as their preferred mode choice.Keywords:  Psychological mechanism, daily activity-travel participation, Bandung metropolitan area